Comparison of intravenous vs intravenous with step-down to oral antibiotic treatment course for Streptococcus and Enterococcus bloodstream infections - Kelsey Bouwman; Jacob W. Pierce; Jennifer Emberger; Alexandra Te Stang; Paul Vos; Aaron M. Kipp; Nicole C. Nicolsen (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract